1,25-Dihydroxyvitamin D3 regulates furin-mediated FGF23 cleavage - Han Xie; Isinsu Bastepe; Wen Zhou; Birol Ay; Zara Ceraj; Ignacio A. Portales-Castillo; Eva S. Liu; Sherri-Ann M. Burnett-Bowie; Harald Jüppner; Eugene P. Rhee; Murat Bastepe; Petra Simic (JCI Insight, 2023)
Intact fibroblast growth factor 23 (iFGF23) is a phosphaturic hormone that is cleaved by furin into N-terminal and C-terminal fragments. Several studies have implicated vitamin D in regulating furin in infections. Thus, we investigated the effect of 1,25-dihydroxyvitamin D3 [1,25(OH)2D] and the vitamin D receptor (VDR) on furin-mediated iFGF23 cleavage. Mice lacking VDR (Vdr–/–) had a 25-fold increase in iFGF23 cleavage, with increased furin levels and activity compared with wild-type (WT) littermates. Inhibition of furin activity blocked the increase in iFGF23 cleavage in Vdr–/– animals and in a Vdr-knockdown osteocyte OCY454 cell line. Chromatin immunoprecipitation revealed VDR binding to DNA upstream of the Furin gene, with more transcription in the absence of VDR. In WT mice, furin inhibition reduced iFGF23 cleavage, increased iFGF23, and reduced serum phosphate levels. Similarly, 1,25(OH)2D reduced furin activity, decreased iFGF23 cleavage, and increased total FGF23. In a post hoc analysis of a randomized clinical trial, we found that ergocalciferol treatment, which increased serum 1,25(OH)2D, significantly decreased serum furin activity and iFGF23 cleavage, compared with placebo. Thus, 1,25(OH)2D inhibits iFGF23 cleavage via VDR-mediated suppression of Furin expression, thereby providing a mechanism by which vitamin D can augment phosphaturic iFGF23 levels.